Modelling cost-effectiveness of tenofovir for prevention of mother to child transmission of hepatitis B virus (HBV) infection in South Africa - Jolynne Mokaya; Edward A. O. Burn; Cynthia Raissa Tamandjou; Dominique Goedhals; Eleanor J. Barnes; Monique Andersson; Rafael Pinedo-Villanueva; Philippa C. Matthews (BMC, 2019)
Abstract Background International sustainable development goals for the elimination of viral hepatitis as a public health problem by 2030 highlight the need to optimize strategies for prevention, diagnosis and treatment of hepatitis B virus (HBV) infection. An important priority for Africa is to have affordable, accessible and sustainable prevention of mother to child transmission (PMTCT) programmes, delivering screening and treatment for antenatal women and implementing timely administration of HBV vaccine for their babies. Methods We developed a decision-analytic model simulating 10,000 singleton pregnancies to assess the cost-effectiveness of three possible strategies for deployment of tenofovir in pregnancy, in combination with routine infant vaccination: S1: no screening nor antiviral therapy; S2: screening and antiviral prophylaxis for all women who test HBsAg-positive; S3: screening for HBsAg, followed by HBeAg testing and antiviral prophylaxis for women who are HBsAg-positive and HBeAg-positive. Our outcome was cost per infant HBV infection avoided and the analysis followed a healthcare perspective. Results Based on 10,000 pregnancies, S1 predicts 45 infants would be HBV-infected at six months of age, compared to 21 and 28 infants in S2 and S3, respectively. Relative to S1, S2 had an incremental cost of $3940 per infection avoided. S3 led to more infections and higher costs. Conclusion Given the long-term health burden for individuals and economic burden for society associated with chronic HBV infection, screening pregnant women and providing tenofovir for all who test HBsAg+ may be a cost-effective strategy for South Africa and other low/middle income settings.